The Paradox of Love of Money and Ethical Culture: Seeking New Insights into Fraud Prevention at The Village Level - Muwahhidin, Muwahhidin; Ansar, Muhammad (International Ecsis Association, 2024)
This study investigates the influence of Love of Money, individual morality, and organizational ethical culture on the tendency of fraud among village officials managing finances in the South Dampal District. The study involved purposive sampling, with 104 respondents who were directly responsible for financial management in villages. Primary data were collected through structured questionnaires and analyzed using multiple linear regression with the Partial Least Square (SmartPLS) application version 4. The findings indicate that Love of Money has no significant effect on the tendency of fraud, while individual morality negatively influences fraud tendency. In contrast, organizational ethical culture does not show a measurable impact. This research contributes to the development of theoretical frameworks by integrating Love of Money, individual morality, and organizational ethical culture as parameters for assessing fraud propensity in village financial management. Practically, the study offers valuable insights for stakeholders and policymakers in enhancing oversight mechanisms to ensure integrity and professionalism in financial management. By fostering ethical culture and reinforcing individual morality among village officials, fraudulent practices in village finances can be minimized. The results underscore the need for continuous oversight and awareness programs to safeguard the ethical and moral dimensions of financial management processes, thereby promoting transparency and accountability in village administrations.